Oxidative/Nitrosative Stress and Brain Involvement in Sepsis: A Relationship Supported by Immunohistochemistry - Bertozzi, Giuseppe; Ferrara, Michela; Calvano, Mariagrazia; Pascale, Natascha; Di Fazio, Aldo (Medicina (Kaunas, Lithuania), 2024)
Background and Objectives: A large amount of recent evidence suggests that cellular inability to consume oxygen could play a notable part in promoting sepsis as a consequence of mitochondrial dysfunction and oxidative stress. The latter could, in fact, represent a fundamental stage in the evolution of the “natural history” of sepsis. Following a study previously conducted by the same working group on heart samples, the present research project aims to evaluate, through an immunohistochemical study, the existence and/or extent of oxidative stress in the brains of subjects who died due to sepsis and define, after reviewing the literature, its contribution to the septic process to support the use of medications aimed at correcting redox anomalies in the management of septic patients. Materials and Methods: 10 cases of subjects who died in healthcare facilities with ante-mortem clinical-laboratory signs that allowed the diagnosis of septic shock were selected as case studies, and 1 case of a subject who died immediately following a road traffic accident was used as a negative control. Samples of the cerebral cortex were then taken, fixed in formalin, and subjected to sections on which an immunohistochemical study was performed using anti-NOX-2, NT, iNOS, and 8-OHdG antibodies. Results: The results emerging from the present study demonstrate that despite a variable expressivity for the NT, iNOS, and NOX2 markers, the brain samples demonstrated univocal and high positivity for the 8-OHdG marker. Conclusions: This would allow us to hypothesize how, regardless of the mechanism of production of ROS and NOS (iNOS or NOX2 mediated) and the pathophysiological mechanisms that are triggered during sepsis, oxidative damage to DNA represents the event to which this whole process leads and, in fact, in the literature, is directly correlated to sepsis-dependent mortality. Neurons, conversely, appear to be more sensitive to oxidative stress because of a low number of protective or scavenger molecules (catalase, glutathione peroxidase, GSH, or vitamin E). Therefore, despite reduced production, the manifestation of the damage remains high. This evidence, together with that of the previous study, can only support the introduction of substances with an antioxidant function in the guidelines for the treatment of sepsis.